(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the association between salivary cortisol levels and periodontal disease. Methods: A cross-sectional study was conducted on 174 patients who visited the Ho Chi Minh city Hospital of Odonto-Stomatology for examination and treatment. They were divided into 3 groups: H (healthy periodontal tissue), G (gingivitis), P (periodontitis). Periodontal tissue was examined and PPD, CAL, BOP, and PI indices were recorded; unstimulated saliva samples were taken. The significance threshold p < 0.05 was applied to all statistical tests. Results: Salivary cortisol levels were significantly greater in the 2 periodontal disease groups compared to the healthy group, with group G showing the highest level (p < 0.05). No association was found between salivary cortisol and BOP, PI, and severity of periodontal disease (p > 0.05). Conclusion: An initial association was discovered between salivary cortisol levels and the presence or absence of periodontal disease. Further research is needed to better define the association between cortisol and periodontal disease.